Early exchange transfusion to treat neonates with gestational alloimmune liver disease: an 11-year cohort study - Fischer, Hendrik S.; Staufner, Christian; Sallmon, Hannes; Henning, Stephan; Bührer, Christoph (Journal of pediatric gastroenterology and nutrition, 2020)
Objectives: Exchange transfusion (ET) and intravenous immunoglobulin are potentially life-saving treatment options in newborns with gestational alloimmune liver disease (GALD). Since 2008, early ET has been the standard of care for symptomatic neonates with suspected GALD in our unit. The present study's aim was to investigate the outcomes of this approach. Methods: From 2008 to 2018, all neonates who received ET for suspected GALD were identified, and their clinical course and outcomes were analyzed in a descriptive cohort study. In survivors, liver function parameters before ET and maximum values after ET and at discharge were compared. - Results: During the 11-year period, 12 infants received ET for suspected GALD at a median (range) chronological age of 11 (1-23) days and gestational age of 38 (32-40) weeks. Signs of impaired liver function, most frequently postnatal hypoglycemia, hyperferritinemia, direct hyperbilirubinemia, and coagulopathy, were present in all infants. Survival without a liver transplant in the overall cohort was 10 of 12 (83.3%) and 7 of 9 (78%) in those fulfilling the criteria of acute liver failure. Two patients died, one of them after liver transplantation. Direct bilirubin typically increased after ET, even in survivors. All survivors recovered and were discharged from the pediatric hepatology outpatient clinic after 8 (3-11) months of follow-up. Conclusions: In newborns with suspected GALD, a limited diagnostic work-up followed by early ET may lead to favorable outcomes. More data are required to develop an evidence-based clinical approach to GALD.
Gesehen am 24.09.2020